Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Pada Perusahaan Elektronik Menerapkan Metode Profile Matching - Tedy Hardiyanto; Fernando Fernando; Errissya Rasywir (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
CV. Bunyamin Central Tehnik – Hartech Jambi is one of the companies that are located in the Jambi area that processing data selection best employee get problems occur like election process employees best the absence of computerized system and still not use a method of the support system decisions, so election employees best cannot be measured , and election process employees best is not transparent because they the evaluation process of employee performance only done by managers and unknown by employees. Hence, this study aims to give solution to problem that happens by offering decision support system of selection best employee using PHP programing language and DBMS MySQL. Writer expand the system with waterfall and methods used the system modeling unified language using use case diagram, activity diagram, class diagrams and flowchart diagram. The new system produce outputs that can data showing employees, data admin, data criteria, the sub criteria, the data employees and the results of selection best employee with profile matching methods who contributed to a company can improve performance and spirit of employees